Effects of a Green Oat Herb Extract on Cognitive Performance and Neurophysiological Activity: A Randomized Double-Blind Placebo-Controlled Study - Martinez-Horta, Saul; Ivanir, Eran; Perrinjaquet-Moccetti, Tania; Keuter, Matthias Heinrich; Kulisevsky, Jaime (Frontiers in Neuroscience, 2021)
Green oat extracts have been used for centuries in traditional medicine in view of their supposed beneficial effects on cognition and mood. Recently, a specific green oat formulation (Neuravena®) showed to have significant bioactive compounds potentially associated with the enhancement of processing speed, working memory and attention. The main aim of the current study was to compare the potential effect of acute administration of 800 mg of Neuravena® with placebo on a set of neurophysiological correlates of processing speed, attention, performance-monitoring and inhibitory control. Twenty healthy participants were randomized to receive either Neuravena® or placebo. Electroencephalographic (EEG) signal acquisition was obtained while participants carried out the modified Eriksen flanker and oddball tasks. Both groups were compared on measures of behavioral task performance, and a set of event-related potentials (ERPs) components related to performance monitoring (the error-related negativity; ERN and the N2), target detection, and attention (P3a/P3b). Following active-intervention N2, ERN, and P3a/P3b were significantly reduced and performance was faster, with no loss of accuracy. Conversely, no neurophysiological differences were found in the placebo group before and after treatment and performance worsened significantly in terms of reaction time and accuracy. Acute administration of 800 mg of Neuravena® appears to enhance the optimization of neural resources and positively influences cognitive performance in tasks associated with executive functions, processing speed and attention. Moreover, Neuravena® prevents the deleterious effects of tiredness during task performance.